Strategic innovation of business models by leveraging demand and supply chains in dynamics ecosystems - Ewouba-Biteghe, Benjamin Simplice (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MComm (Business Management))--University of Stellenbosch, 2006.